Penerapan Prinsip Keberlanjutan: Strategi Negara Menurunkan Emisi Karbon? - Permatasari, Anita (Uti Possidetis: Journal of International Law, 2022)
As one of Indonesia's leading commodities, the trend of palm oil exports is always increasing. Even so, this commodity is often subject to global market discrimination which is manifested through regulations and policies of countries consuming palm oil commodities, such as the Renewable Energy Directive II (RED II) and the proposal for Regulation on deforestation-free products. The Indonesian government has filed a lawsuit against this regulation, but the WTO dispute resolution mechanism is still considered unable to resolve the problem, especially the reason that consumer countries think that Indonesian palm oil can reduce its post-2020 emission reduction commitments under the Paris Agreement through Nationally Determined Contributions (NDCs) which needs to be fulfilled in 2030. On the other hand, the Government of Indonesia still needs to improve the governance of Indonesian palm oil in order to increase the acceptance of this commodity in the global eyes. This study aims to find a middle ground for commitments to reduce emissions from consumer countries and improve Indonesian palm oil governance through the acceptability of the palm oil market which is realized through free trade agreements. The formation of a trade agreement by including a clause on sustainability can be one solution to reconcile the acceptance of the palm oil market and global climate change commitments.